Nusyuz dalam Perspektif Hadis: Analisis Hukum, Hikmah, dan Relevansinya di Era Modern - Nida Rafiqa Izzati; Bagus Kusumo Hadi; Adam Dewantara Putra; Sri Jati Ratna Sari (Al-Hasyimi: Jurnal Ilmu Hadis, 2024)
This article discusses the concept of nusyuz from the perspective of hadith, aiming to understand its position, legal rulings, and the wisdom behind the prohibition of nusyuz in marital relationships, as well as its relevance in the modern era. Nusyuz, which can be committed by either a husband or a wife, refers to an attitude of defiance or disobedience towards a spouse, such as neglecting rights or failing to fulfill respective obligations. Using a qualitative research method with a library research approach, this article analyzes various hadiths related to nusyuz through approaches such as tahlil lafdzi (linguistic analysis), ma’nal ijmali (general understanding), sabaabul wuruud (context of hadith), and fiqhul hadith (understanding of the legal implications in the hadith). The findings show that a husband has the right to discipline a wife who is nusyuz, while the wife is obligated to obey her husband as long as it aligns with Islamic principles and does not involve sin. Conversely, a wife can also take specific steps if her husband commits nusyuz. If the conflict becomes severe and unresolvable, it is recommended to involve a third party as a mediator to maintain the harmony of the household. These findings highlight the seriousness of Islam's concern for the husband-wife relationship and the importance of preserving family unity based on Islamic teachings. This study is expected to serve as a reference for understanding the concept of nusyuz from an Islamic legal perspective and provide practical guidance for married couples in resolving conflicts in their household life